Promoting pro-environmental printing behavior: The role of ICT barriers and sustainable values - Javed Suleri; Elena Cavagnaro (Dutch Journal of Finance and Management, 2016)
This study aims to explore how to reduce printing at elementary schools through strengthening both the effective use of ICT and pro-environmental values. Literature review is presented in themes - ICT barriers (fears, knowledge, skills and time), demographic, printing behavior and sustainable values (egoistic, hedonic, prosocial & biospheric). A quantitative method is applied in this study, data is obtained from 108 teachers from seven elementary schools at three different regions in Northwest Friesland, The Netherlands by using a questionnaire. The value scale by De Groot and Steg (2008) is applied for sustainable values while for ICT barriers and printing behavior, questions are developed by the author and validated by Cronbach. The main findings illustrate that lower ICT fears and higher biospheric values have a positive effect on the pro-environmental printing behavior. To minimize teachers' ICT fears and printing, directors of the schools should train teachers in the use of ICT and enhance their biospheric values. This study is one of the first to explore ICT barriers with the combination of pro-environmental values orientation contributing pragmatic evidence to reducing financial and environmental costs.
Keywords: 650; ICT integration; onscreen reading; green printing; pro-environmental behavior; Sustainability and ICT